If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-3v + 1) = 5(-2v + -2) Reorder the terms: 2(1 + -3v) = 5(-2v + -2) (1 * 2 + -3v * 2) = 5(-2v + -2) (2 + -6v) = 5(-2v + -2) Reorder the terms: 2 + -6v = 5(-2 + -2v) 2 + -6v = (-2 * 5 + -2v * 5) 2 + -6v = (-10 + -10v) Solving 2 + -6v = -10 + -10v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '10v' to each side of the equation. 2 + -6v + 10v = -10 + -10v + 10v Combine like terms: -6v + 10v = 4v 2 + 4v = -10 + -10v + 10v Combine like terms: -10v + 10v = 0 2 + 4v = -10 + 0 2 + 4v = -10 Add '-2' to each side of the equation. 2 + -2 + 4v = -10 + -2 Combine like terms: 2 + -2 = 0 0 + 4v = -10 + -2 4v = -10 + -2 Combine like terms: -10 + -2 = -12 4v = -12 Divide each side by '4'. v = -3 Simplifying v = -3
| 100-93+(-83)+(-48)= | | 3b+2=144 | | 8x^2+3=10x | | (-10)-3+96-98= | | 4x^2+27=12 | | 8n-1-7=24 | | 760-40x=210+70x | | 4x+4=2x+24 | | 2(3p+4)+9p=38 | | -3x=2x-55 | | 760x-40=210+70 | | (-71)+94+(-33)+91= | | -1+6v=8v+11 | | -(-4-8n)=-8n-4(5-3n) | | -5(3b+8)=45 | | -24-9-(-36)+(-92)= | | -4-5x=116+5x | | a-3b+a+5b/(a+b) | | 2x-4(1+5x)=2-2(x+3) | | 2(a+3)=3(9-a) | | 1/2(6x+5) | | 14/8+2/3 | | 7c+6d-5(4c-3d)= | | 13-13x=(4x+3)(x-1) | | -3(4-3n)=-n-4(7n+3) | | 7x+1=-5x-47 | | -12=y/-13 | | -2(4x+7)=-8x+14 | | 4*5x=6 | | 15/8+2/3 | | 6/9+8/9 | | 24=8(4y+1) |